1972
DOI: 10.1016/0005-2760(72)90075-6
|View full text |Cite
|
Sign up to set email alerts
|

Some studies on the biosynthesis of the molecular species of phosphatidylcholine from rat lung and phosphatidylcholine and phosphatidylethanolamine from rat liver

Abstract: SUMMARYr.Atdifferent timeintervals afterinjectionof [r(3)-SH]glycerol, theincorporation of glycerol into the various molecular species of phosphatidylcholine and phosphatidylethanolamine from rat liver, and phosphatidylcholine from rat lung was determined.2. The results indicate that, in liver, a de rtovo synthesis is primarily operating in the biosynthesis of linoleic acid-containing molecules of lecithin and of the hexaenoic molecular species of phosphatidylethanolamine. An acylation of monoacyl derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The livers were removed and homogenized in 0.33 M sucrose/O.01 M Tris (pH 7.4) with the aid of a Potter-Elvehjem homogenizer (1 g liver/IO ml). The microsomal and 105,OOOg supematant fractions were isolated from the liver homogenates as described previously (13). The microsomal pellets were resuspended in 0.125 M KCX0.1 M Tris (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The livers were removed and homogenized in 0.33 M sucrose/O.01 M Tris (pH 7.4) with the aid of a Potter-Elvehjem homogenizer (1 g liver/IO ml). The microsomal and 105,OOOg supematant fractions were isolated from the liver homogenates as described previously (13). The microsomal pellets were resuspended in 0.125 M KCX0.1 M Tris (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…No evidence was found for the existence of phospholipase A activity in lamellar bodies. 4. The microsomal phospholipase A, was more active towards phosphatidylcholines containing an unsaturated fatty acid at the 2-position than towards the disaturated phosphatidylcholines.…”
Section: Discussionmentioning
confidence: 92%
“…Both studies in vivo [4,5] and in vitro [6,7] have shown, however, that the principal ~hosphatidylcholines synthesized de novo are species which contain palmitic acid at the l-position and an unsaturated fatty acid at the S-position. Thus, the synthesis of dipalmitoylphosphatidylcholine must be the result of a mechanism which replaces the unsaturated fatty acid at the 2-position with palmitic acid.…”
Section: Discussionmentioning
confidence: 99%
“…There are several differences in the utilization of diacylglycerol by cholineand ethanolaminephosphotransferase [27,28], the latter one showing a preference for highly unsaturated species. It is very well possible that the newly formed diacylglycerol is a better substrate for ethanolaminephosphotransferase, which would explain the increase in the incorporation of ethanolamine into phosphatidylethanolamines.…”
Section: Discussionmentioning
confidence: 99%